INVESTIGATION OF FERMENTED FOODS FOR ISOLATION OF BENEFICIAL PROBIOTIC MICROORGANISMS - Zeinah Abdul Ameir Mohammed; Farqad Abdullah Rashid (Scholars Digest Publishing, 2025)
A "potential probiotic" refers to a microorganism that has the potential to confer health benefits when consumed. Probiotics are beneficial bacteria, or they can be known as friendly to human health, especially for the digestive system, because they are very beneficial to the intestines. In the current study, we highlight products that contain therapeutic alternatives for human health found in home-fermented foods, as well as those available in local markets, where tests were positive for the presence of probiotics in these foods. Out of 50 samples, there were 60 isolates, of which only 40 belonged to Lactic acid bacteria LAB, and the appearance on MRS agar media is shown white, large, smooth, little convex, little mucoid, and round colonies with entire margin, under the microscope, The cells exhibited a positive reaction to Gram staining, presenting as purple rods or cocci with rounded ends, occurring individually, in pairs, or in short chains, and non-spore-forming, and the biochemical characteristics of the catalase and oxidase tests were negative, there were two genera, Lactobacillus and Lactococcus as a potential probiotic found in foods. The twenty isolates were excluded because they were growing with difficulty on MRS medium and had different shapes and colours of colonies, also the cells under the microscope had a negative Gram stain, while oxidase and catalase tests were positive.
Keywords: Bacteria, Lactic acid bacteria, Lactobacillus, Lactococcus, probiotics, Gram-positive, Gram-negative.